Opening of the Deep Layers of The Side Face in Processes of Purulous Inflammation (Texas Journal of Multidisciplinary Studies, 2023)
Purulent inflammatory processes on the face side can lead to severe consequences if not treated in a timely and effective manner. Opening deep floors in such cases is a decisive step towards successful management. This article aims to explore the importance of this procedure to present a comprehensive and informative discussion.